What Do You Meme, Professor? An Experiment Using “Memes” in Pharmacy Education - Joshua D. Brown (Pharmacy, 2020)
Memes are social or cultural constructs and ideas dispersed from person to person. The modern definition of memes applies to images, photographs, or videos shared on digital platforms juxtaposed with text that utilizes the emotion, meaning, or joke behind the original “meme” to communicate the author’s message. Younger generations of learners are more prone to utilize digital and social media to distribute and consume information and use of these platforms has increased in modern classrooms. However, there are few examples of using memes for educational purposes, including student-generated content, and no known examples in pharmacy education. This commentary introduces the concept of a meme and describes an attempt to incorporate a student-generated meme assignment in a pharmacy course. Experiences and lessons learned are discussed as words of caution in incorporating and evaluating memes or other informal communication tools for educational purposes.